2003
DOI: 10.1080/0144361031000153701
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum fetal head circumference and its influence on labour duration in nullipara

Abstract: A retrospective analysis of postpartum fetal head circumference (FHC) and birth weight and its effect on the duration of labour was undertaken. The aim was to assess the predictive value of postpartum FHC versus birth weight in predicting dystocia. A FHC > 37 cm was associated significantly with a prolonged first and second stage of labour. A receiver operator curve (ROC) shows that the sensitivity and specificity of a FHC > 37 cm is as good as a fetal weight > 4.5 kg in predicting dystocia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…Therefore we excluded women with an estimated foetal weight above 4000 grams. Importantly, a previous study by Zaretsky et al [18] eliminated cases of macrosomia and large foetal head circumference, which are well-known to effect normal progress of labour [23]. Surprisingly, Ferguson et al assessed a high-risk group for obstructed labour based on previous delivery and risk factors in the current pregnancy and did not find an association between foetal head parameters and obstructed labour [24].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore we excluded women with an estimated foetal weight above 4000 grams. Importantly, a previous study by Zaretsky et al [18] eliminated cases of macrosomia and large foetal head circumference, which are well-known to effect normal progress of labour [23]. Surprisingly, Ferguson et al assessed a high-risk group for obstructed labour based on previous delivery and risk factors in the current pregnancy and did not find an association between foetal head parameters and obstructed labour [24].…”
Section: Discussionmentioning
confidence: 98%
“…A recent population-based Swedish study that evaluated postnatal head circumference suggested that women delivering infants with large FHC (39-41 cm) were significantly more likely to experience vacuum-assisted vaginal delivery, fetal distress, prolonged labor and cesarean section relative to women delivering infants with average FHC [9]. Among nulliparous Irish women, large FHC was significantly associated with prolonged labor with similar sensitivity and specificity as elevated birth weight [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the impact of head circumference on the odds of operative delivery in nulliparae; [6][7][8]10 rather focusing on estimated fetal weight. 11 The earlier studies showed that the odds of operative delivery and prolonged second stage of labor 6-8 increased as HC increased, and found as we did that infants of higher birth weight were less likely to show signs of fetal distress than smaller fetuses with similar HC 6 .…”
mentioning
confidence: 97%
“…the tension at the point of meeting of the human fetal head and the bipedal female pelvis, [1][2][3][4] but sparse attention has been paid in the obstetric literature to the impact of head circumference on obstetric outcomes. [5][6][7][8][9][10] The literature on problems of delivery in "big babies" focuses primarily on fetal size in terms of weight. [11][12][13][14] We queried how fetal head dimensions might impact the passage of the fetus through the birth canal and affect obstetric outcomes, primarily delivery mode.…”
mentioning
confidence: 99%